ETYMOLOGY AND SEMANTIC ANALYSIS OF THE NAMES OF FAMOUS ITALIAN DISHES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines the etymology and semantics of the names of well-known Italian dishes, revealing their role as cultural markers and symbols of national identity. The study combines linguistic, historical, and cultural analyses to explore how historical events, regional traditions, and social transformations influenced the formation of gastronomic terms such as pizza, pasta, lasagna, tiramisù, and carbonara.